Inkheart - Funke, Cornelia Caroline (Chicken House/Scholastic, 2003)
Twelve-year-old Meggie learns that her father Mo, a bookbinder, can "read" fictional characters to life when an evil ruler named Capricorn, freed from the novel "Inkheart" years earlier, tries to force Mo to release an immortal monster from the story.